Cationic Intermixing and Reactivity at the La2Mo2O9/La0.8Sr0.2MnO3−δ Solid Oxide Fuel Cell Electrolyte–Cathode Interface. Issue 16 (1st August 2016) - Ravella, Uday K.; Liu, Jingjing; Corbel, Gwenaël; Skinner, Stephen J.; Lacorre, Philippe
Abstract: Among standard high‐temperature cathode materials for solid oxide fuel cells, La0.8 Sr0.2 MnO3− δ (LSM) displays the least reactivity with the oxide‐ion conductor La2 Mo2 O9 (LMO), yet a reaction is observed at high processing temperatures, identified by using XRD and focused ion beam secondary‐ion mass spectrometry (FIB‐SIMS) after annealing at 1050 and 1150 °C. Additionally, Sr and Mn solutions were deposited and annealed on LMO pellets, as well as a Mo solution on a LSM pellet. From these studies several reaction products were identified by using XRD and located by using FIB‐SIMS on the surface of pelletised samples. We used depth profiling to show that the reactivity extended up to ∼10 μm from the surface region. If Sr was present, a SrMoO4 ‐type scheelite phase was always observed as a reaction product, and if Mn was present, LaMnO3+ δ single crystals were observed on the surface of the LMO pellets. Additional phases such as La2 MoO6 and La6 MoO12 were also detected depending on the configuration and annealing temperature. Reaction mechanisms and detailed reaction formulae are proposed to explain these observations. The strongest driving force for cationic diffusion appears to originate from Mo 6+ and Mn 3+ cations, rather than from Sr 2+ . Abstract : Phase time : The reactivity between La2 Mo2 O9 and La0.8 Sr0.2 MnO3− δ is investigated at up to 1150 °C by using secondary‐ion mass spectrometry and XRD. We observe the formation of a range of intermediate phases, which suggests significant cation mobility in these materials. Potential reaction pathways are discussed, which includes the formation of SrMoO4, Mn3 O4, and LaMnO3, and a unified expression to describe this process is identified.